Vivendo casamentos, separações e recasamentos: um estudo sobre o campo representacional da conjugalidade - Martins, Priscilla de Oliveira (2009)
The object of the research is conjugality. To study conjugality is important to comprehend a reality that seems paradoxal at surface: there is a rise in divorce and separation numbers, but at the same time, it is verified that marriage is still considered by people as an important aspect of life. In that way the present research aims to identify the representational field of conjugality and its relation with the day to day marital praxis. The Social Representational Theory was used to base the analyses. The methodological design used was the qualitative approach. The data was collected by focus groups. Six focus groups were held. Three groups had women as participants and three focus groups had men as participants. The criteria to choose the participants to take part in the study were: Group 1: persons who were married for 10 years or less; Group 2: persons who were divorced or separated; Group 3: persons who were in a second marriage. All the participants also had to have at least one child at the first marriage and live on a considered middle and upper high class neighborhood. The results present the representational field of conjugality as formed by social representations objects of love, marriage/ remarriage and divorce/separation. There are social representational elements which are shared by all groups and elements which are specific considering sex. The shared elements which form the conjugality representational field present the conjugality as a partnership based on love, complicity and respect. The divorce/ separation is social represented as a frustration and a breakdown of a conjugality dream. The women, specifically, represented the conjugality as a space where they have to give themselves for the marriage well being and takeover wife and mother roles. The social representation of marriage presents idealized/ romanticized elements that can change along the day to day marriage life. To the men, the specific elements present conjugality as a space where dedication and hard work are necessary in order to maintain it. An important element to conjugality success is the wife´s active role, contrary of the docile, submissive wife. Marriage is represented as a ritual and a tradition in which fidelity is important. The representational field analyses present elements referring to traditional gender roles and elements referring to a more equalitarian relationship. The representational field anchoring analyses showed that satisfaction and happiness seems to be the elements that direct the anchoring process. The representational field identified orients to a praxis in which the conjugality is lived as an affectionate space where both couple members need to be satisfied. Upon this perspective, negotiation is the essential tool for a loving relationship success.